The critical region of overlap defining theAZFa male infertility interval of proximal Yq contains three transcribed sequences. Issue 9 (1st September 1999) - Sargent, Carole A; Boucher, Catherine A; Kirsch, Stefan; Brown, Graeme; Weiss, Birgit; Trundley, Anita; Burgoyne, Paul; Saut, Neomie; Durand, Christine; Levy, Nicolas; Terriou, Philippe; Hargreave, Timothy; et al.
Abstract : The position of deletion breakpoints in a series of four AZFa male infertility patients has been refined using new markers derived from BAC clone DNA sequence covering the AZFa male infertility interval. The proximal half of the AZFa interval is occupied by pseudogene sequences with homology to Xp22. The distal half contains an anonymous expressed sequence tag (named AZFaT1) found transcribed in brain, testis, and skeletal muscle and the DFFRY and DBY genes. All the patients have AZFaT1 and DFFRY deleted in their entirety and three patients additionally have DBY deleted. The three patients with AZFaT1, DFFRY, and DBY deleted show a severe Sertoli cell only syndrome type I phenotype, whereas the patient that has retained DBY shows a milder oligozoospermic phenotype. The expression of DBY in a cell line from this latter patient is unaltered; this shows that it is the loss of genes lying within the deletion that is responsible for the observed oligozoospermia. RT-PCR analysis of mouse testis RNA from normal and XX Sxr a mice (devoid of germ cells) has shown that Dby is expressed primarily in somatic cells and that the level of expression is unaltered during germ cell differentiation. This contrasts with Dffry where no transcripts are detectable in XX Sxr a mouse testis and expression occurs specifically in testis mRNA in a germ cell dependent fashion.